Mathematical modeling of deformation during the flatcardboard creasing - Poliezhaiev, Ivan; Gavva, Oleksandr M. (My University, 2015)
The relevance and the way of flat paperboard creasing mathematical modeling with the finite element method are described in the article. The quality of creasing is influenced by many factors, the main ones are the physical and mechanical properties and structure of paperboard, shape and size of creasing tools and parameters of creasing matrix. Mathematical model of creasing allows predicting the influence of these factors on the process of creasing and quality, and selecting rational parameters.
Keywords: creasing; cardboard; paperboard deformation; paperboard folding; бігування картону; картон; деформація картону; складання картону; кафедра машин і апаратів харчових та фармацевтичних виробництв